Synthesis and cytotoxicity of polyhydroxylated cholesterol derivatives - Dinh Thi Ha,; Doan Lan Phuong,; Pham Quoc Long,; Ngo Dai Quang,; Tran Thi Thu Thuy , (Vietnam Journal of Science and Technology, 2018)
Eight polyhydroxylated cholesterol derivatives (1-8) were prepared from cholesterol, using oxidative reagents as SeO2, OsO4/NMO, HCOOH/H2O2 and BH3/ H2O2. Their structures were elucidated by using physical methods including NMR 1D and 2D. These compounds were evaluated against two cancer cell lines (Hep-G2, T98). Compounds 2, 4 and 8 inhibits human hepatocellular carcinoma cell line (Hep-G2) with IC50 4.69, 4.98 and 2.89 µg/mL, respectively. In addition, compound 8 exhibited strong cytotoxicity against T98 cell line (glioblastoma) with IC50 = 2.28 μM.